2022
DOI: 10.1021/acsaem.2c00755
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties’ Synergy of Stretched P(VDF-HFP) and P(VDF-HFP)/PMMA Blends Creates Ultrahigh Capacitive Energy Density in All-Organic Dielectric Films

Abstract: Dielectric capacitors with a high energy-storage density and efficiency are urgently required for miniaturization and integration of power electronics and pulsed power system. Herein, single-layered stretched P­(VDF-HFP) with a certain content of poly­(methyl methacrylate) (PMMA) and two kinds of sandwich-structured films are prepared to optimize and compare energy-storage performance. The results revealed that the crystallization transition behavior of stretched P­(VDF-HFP) films contributed to enhance its el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…As another strategy, all-organic PVDF-based blends have been embraced and employed because of their good compatibility, similar physicochemical properties and easy machining performance. 24,25 For example, methyl methacrylate–butadiene–styrene copolymer (MBS) 26 and thermoplastic polyurethane (TPU) 27 have been incorporated into PVDF, respectively, and then all-organic PVDF-based composite films were obtained with both improved E b and U d . The results demonstrated that the organic fillers exhibited better compatibility with PVDF than the inorganic fillers and further helped to suppress the breakdown damage at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…As another strategy, all-organic PVDF-based blends have been embraced and employed because of their good compatibility, similar physicochemical properties and easy machining performance. 24,25 For example, methyl methacrylate–butadiene–styrene copolymer (MBS) 26 and thermoplastic polyurethane (TPU) 27 have been incorporated into PVDF, respectively, and then all-organic PVDF-based composite films were obtained with both improved E b and U d . The results demonstrated that the organic fillers exhibited better compatibility with PVDF than the inorganic fillers and further helped to suppress the breakdown damage at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…20,70,82 When the frequency was increased from 1 kHz to 1 MHz, the change of the dielectric constant of PMMA-BT was less than 13%. Moreover, the change of the dielectric constant with the frequency was not affected by the concentration of BaTiO 3 nanoparticles, and the polymer nanocomposite showed better frequency stability than the latest reported core-shell or sandwich-structured PMMA/BaTiO 3 system, 8,20,68,73,74 which was attributed to the improvement of the two-phase interface in the system and the dipoles could follow the external electric field change at high frequency. 71,72 With the increase of BT content, the dielectric constant of the capacitor increased accordingly.…”
Section: Dielectric Constant and Dielectric Lossmentioning
confidence: 82%
“…31 Meanwhile, they could also build up a higher energy barrier for carrier injection, leading to enhanced E b and improved energy storage performance. 12,32,33 The most adopted strategy to construct the perpendicular interfaces is the sandwich structure, which could be constructed through hot pressing, 10,13 layer-by-layer assembly, 34−37 and multilayer coextrusion. 14,16,38−40 However, those methods limit the fabrication of multicomponent all-organic polymer dielectric films on an industrial scale to some extent.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In general, polymers with high ε r , such as poly­(vinylidene difluoride) (PVDF)-based homo- or copolymers, and polyamide (PA)-based homo- or copolymers, were widely expected as the preferred component to achieve high energy storage performance in multicomponent all-organic polymer dielectric films. However, the large polarity of these polymers causes the incompatibility between them and PP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation